E-governance gaining in popularity - Rao, Radhakrishna (2003)
E-governance is the best option to remove the barriers between the people and the administration at all levels of the functioning of a democratic Government. It is a bold attempt at transforming administration into a people friendly, transparent and accountable preposition. E-Governance concept involves delivering a variety of services via the internet, telephone community centres or Government departments with a view to transform the Government from being a "procedures and power-centred mechanism" to "citizen and service-centred platform". - Reproduced.
Keywords: Electronic governance